PENGARUH SISTEM PENGENDALIAN INTERN DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH TERHADAP GOOD GOVERNANCE (STUDI EMPIRIS DI KABUPATEN MINAHASA) - Prabawa, Sigit; Karamoy, Herman; Mawikere, Lidia (Universitas Sam Ratulangi, 2020)
The reform era demands that governments run governance by being based on good governance. This research aims to prove empirically the influence of internal control system implementation and accountability of regional financial management to the efforts to realize good governance in Minahasa district. The type of research used is quantitative research with a descriptive approach. The population in this study was 211 Echelon III in 33 SKPD in Minahasa District as well as sample selection using purposive sampling technique. Data collection is conducted by spreading questionnaires on 65 respondents in 32 SKPD. Data is processed using SPSS program version 25. Data analysis methods use multiple linear regression analyses and t tests to partially test hypotheses. The results showed that 1) the internal control system has a positive and significant effect on the efforts to realize good governance. 2) Accountability of regional financial management has no positive and significant effect on the efforts to realize good governance.